A WHO-HPH operational program versus usual routines for implementing clinical health promotion: an RCT in health promoting hospitals (HPH) - Jeff Kirk Svane; Shu-Ti Chiou; Oliver Groene; Milena Kalvachova; Mirna Zagrajski Brkić; Isao Fukuba; Tiiu Härm; Jerneja Farkas; Yen Ang; Mikkel Østerheden Andersen; Hanne Tønnesen (Implementation Science, 2018)
Abstract Background Implementation of clinical health promotion (CHP) aiming at better health gain is slow despite its effect. CHP focuses on potentially modifiable lifestyle risks such as smoking, alcohol, diet, and physical inactivity. An operational program was created to improve implementation. It included patients, staff, and the organization, and it combined existing standards, indicators, documentation models, a performance recognition process, and a fast-track implementation model. The aim of this study was to evaluate if the operational program improved implementation of CHP in clinical hospital departments, as measured by health status of patients and staff, frequency of CHP service delivery, and standards compliance. Methods Forty-eight hospital departments were recruited via open call and stratified by country. Departments were assigned to the operational program (intervention) or usual routine (control group). Data for analyses included 36 of these departments and their 5285 patients (median 147 per department; range 29–201), 2529 staff members (70; 10–393), 1750 medical records (50; 50–50), and standards compliance assessments. Follow-up was measured after 1 year. The outcomes were health status, service delivery, and standards compliance. Results No health differences between groups were found, but the intervention group had higher identification of lifestyle risk (81% versus 60%, p < 0.01), related information/short intervention and intensive intervention (54% versus 39%, p < 0.01 and 43% versus 25%, p < 0.01, respectively), and standards compliance (95% versus 80%, p = 0.02). Conclusions The operational program improved implementation by way of lifestyle risk identification, CHP service delivery, and standards compliance. The unknown health effects, the bias, and the limitations should be considered in implementation efforts and further studies. Trial registration ClinicalTrials.gov: NCT01563575. Registered 27 March 2012. https://clinicaltrials.gov/ct2/show/NCT01563575